2021
DOI: 10.1051/0004-6361/202039102
|View full text |Cite
|
Sign up to set email alerts
|

The best of both worlds: Combining LOFAR and Apertif to derive resolved radio spectral index images

Abstract: Super massive black holes at the centres of galaxies can cycle through periods of activity and quiescence. Characterising the duty cycle of active galactic nuclei (AGN) is crucial for understanding the impact of the energy they release on the host galaxy. For radio AGN, this can be done by identifying dying (remnant) and restarted radio galaxies from their radio spectral properties. Using the combination of the images at 1400 MHz produced by Apertif, the new phased-array feed receiver installed on the Westerbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 89 publications
4
44
0
Order By: Relevance
“…This work can now be complemented with the information on the resolved spectral index obtained using the combination of LOFAR images at 150 MHz and Apertif images at 1400 MHz. A first proof-of-concept was presented in [38]. Despite being limited to a relatively small area (about 6 deg 2 of the LH region), and despite using Apertif science verification data, this study did show the potential of adding the spectral information (even if limited to two frequencies only).…”
Section: Building Large Samples Of Remnant and Restarted Radio Galaxiesmentioning
confidence: 94%
See 3 more Smart Citations
“…This work can now be complemented with the information on the resolved spectral index obtained using the combination of LOFAR images at 150 MHz and Apertif images at 1400 MHz. A first proof-of-concept was presented in [38]. Despite being limited to a relatively small area (about 6 deg 2 of the LH region), and despite using Apertif science verification data, this study did show the potential of adding the spectral information (even if limited to two frequencies only).…”
Section: Building Large Samples Of Remnant and Restarted Radio Galaxiesmentioning
confidence: 94%
“…The noise level ranges between 35 and 40 µJy beam −1 in the regions not affected by imaging artefacts. The flux scale of the Apertif mosaic was checked against the NVSS, as was previously done for the image covering a smaller part of the LH area ( [38]). Similarly, a difference of about 10% in the flux scale was found and corrected for.…”
Section: Exploring the Spatially-resolved Spectral Indices Distribution Of Radio Galaxies In The Lockman Hole Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultra-low frequency data are also crucial for the study of remnants of radio galaxies (Brienza et al 2017;Mahatma et al 2018). Recent investigations have shown that this elusive population of sources exhibits a range of spectral properties and some still show the presence of a faint core (Morganti et al 2020;Jurlin et al 2020). The addition of a very low frequency point for a resolved spectral analysis will constrain the time scale of the 'off' phase.…”
Section: Radio-loud Agnmentioning
confidence: 99%